The Effect of Implementing the Digital Hazard Reporting Website Laporkan.id on the Safety Climate at PT X Surakarta - Annisa Noviani; Haris Setyawan; Nabylla Sharfina Sekar Nurriwanti (Jurnal Kesehatan, 2026)
Manual reporting in construction projects is often underutilized due to time constraints, complex procedures, and lack of feedback from management, resulting in many potential hazards going unreported, increasing the risk of workplace accidents and weakening the overall safety climate. Therefore, implementing a digital reporting platform such as Laporkan.id is expected to make the reporting process easier, faster, and more responsive, thereby encouraging workers to be more actively involved in safety practices and contributing to a stronger safety climate in the organization. This research aims to analyze the impact of implementing the Laporkan.id website on the safety climate at PT X Surakarta. This study employed a quasi-experimental, non-equivalent control-group design, with population was 95 field workers at PT X Surakarta. A sample of 78 workers was selected using proportional stratified random sampling. The data were collected using the Nordic Safety Climate Questionnaire (NOSACQ-50) and analyzed using the Wilcoxon Signed-Rank Test, the Mann-Whitney U Test, and Spearman's Rank Correlation. The Wilcoxon test indicated a significant increase in safety climate scores in the experimental group (p=<0.001). In contrast, the Wilcoxon test for the control group showed no significant change (p=0.285). The Mann-Whitney test revealed a significant difference between the two groups (p=<0.001). Furthermore, Spearman's correlation showed no significant relationship between safety climate and demographic variables, including age, education, length of service, or job section. The researcher advises PT X Surakarta to further implement the Laporkan.id website, a digital platform for hazard reporting, as part of the company's Occupational Health and Safety (OHS) program.